Perovskite quantum dot glass and its preparation method
Through the rapid cold treatment method simplify the preparation process of lymph and ore ore, solve the problem of complex and high cost of existing technology, achieve efficient and simple production, and maintain good luminous performance and stability.
Patent Information
- Application Number
- CN202211687217.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-12-27
AI Technical Summary
The preparation process of existing perovskite quantum dot glass is complex, has high cost and has a long time, making it difficult to meet the simple and efficient production needs.
The rapid cold treatment method is adopted. After hot -melt treatment of the mixture of the glass matrix and the microcrystalline raw material, the mold is used for rapid cold treatment. In a short time, the temperature drops sharply and the energy is rapidly transferred to achieve a few seconds of the quantum dot.
It greatly simplifies the process of crystal, saved time and cost, and the prepared perovskite quantum dot glass has good luminous performance and stability. It maintains a higher PLQY, and the blue light can reach 65 %.
Smart Images

Figure CN115784620B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quantum dot fluorescent glass ceramics, and in particular to perovskite quantum dot glass and a preparation method thereof. Background Art
[0002] All-inorganic CsPbX3 (X = Cl, Br, I) perovskite quantum dots have become a hot topic of research due to their excellent optical properties such as high photoluminescence quantum yield, narrow-band emission and wide color gamut. In recent years, researchers have optimized quantum dot materials from the perspectives of synthesis, structure / performance optimization, etc. Unprecedented progress has been made in the practical applications of quantum dot LEDs, LCDs, lasers, photodetectors and scintillators. However, colloidal CsPbX3 quantum dots prepared by methods such as cation / anion exchange, solvothermal reaction, and hot injection usually have poor long-term stability in the presence of water, heat and light due to the large surface energy of the quantum dots and the influence of their own ionic structure. The non-dense structures obtained by these methods are not sufficient to protect the quantum dots from the external environment. Therefore, CsPbX3 quantum dots are embedded in glass to prepare CsPbX3 quantum dot glass, in which the CsPbX3 quantum dots are isolated by the glass network and well crystallized in the glass matrix, thereby protecting them from the external environment and improving their stability. However, the preparation process of CsPbX3 quantum dot glass is relatively complicated, including high-temperature calcination, annealing and heat treatment processes. On this basis, a simpler method is urgently needed to prepare CsPbX3 quantum dot glass.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] One object of the present invention is to provide a method for preparing perovskite quantum dot glass to solve the technical problems of the prior art that the preparation process of perovskite quantum dot glass is complicated, costly and time-consuming.
[0005] Another object of the present invention is to provide perovskite quantum dot glass prepared by the preparation method of perovskite quantum dot glass.
[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0007] The preparation method of perovskite quantum dot glass comprises the following steps:
[0008] The mixture of the glass matrix and the microcrystalline raw material is subjected to a heat-melting treatment to obtain a molten material; the molten material is placed on a first mold, and a second mold is pressed on the molten material to perform a rapid cooling treatment to obtain a perovskite quantum dot glass;
[0009] The time of the rapid cooling treatment is 5 to 10 seconds.
[0010] In one embodiment, the mixture comprises the following components in parts by weight:
[0011] SiO2 25-35 parts, B2O3 28-37 parts, ZnO 8-14 parts, SrCO3 5-8 parts, NaF 5-10 parts, Cs source 5-10 parts, lead source 3-5 parts and NaBr 2-5 parts.
[0012] In one embodiment, the Cs source includes at least one of cesium carbonate and cesium halide.
[0013] In one embodiment, the lead source includes at least one of lead halide, lead oxide, and lead acetate.
[0014] In one embodiment, the mixture comprises the following components in parts by weight:
[0015] SiO2 26-34 parts, B2O3 29-36 parts, ZnO 7-13 parts, SrCO3 5-7 parts, NaF 6-9 parts, Cs source 6-9 parts, Pb source 3-4 parts and NaBr 2.5-4 parts.
[0016] In one embodiment, the glass matrix and the microcrystalline raw material are ground to obtain the mixture.
[0017] In one embodiment, the mixture has a particle size of 200-500 mesh.
[0018] In one embodiment, the temperature of the hot melt treatment is 1000-1150° C., and the time of the hot melt treatment is 5-15 minutes.
[0019] In one embodiment, the thickness of the first mold and the second mold are respectively 0.5-2 cm.
[0020] In one embodiment, the temperature of the first mold and the second mold is 10-25°C.
[0021] In one embodiment, the ambient temperature of the rapid cooling treatment is 10-25°C.
[0022] The perovskite quantum dot glass is prepared by the method for preparing the perovskite quantum dot glass as described above.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention adopts rapid cooling treatment, the temperature drops suddenly in a short period of time, the energy is quickly transferred, and the quantum dots are crystallized within a few seconds; compared with the traditional heat treatment crystallization method, the crystallization process is greatly simplified, saving time and cost.
[0025] (2) The perovskite quantum dot glass prepared by the present invention has good luminescence performance and stability, and maintains a high PLQY, which can reach 65% under blue light excitation. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The emission spectra of the perovskite quantum dot glasses in Examples 1 to 5 and Comparative Examples 1 to 2 under 420 nm wavelength excitation;
[0028] Figure 2 This is a diagram of the photoluminescence quantum dot efficiency of the perovskite quantum dot glass in Example 1. DETAILED DESCRIPTION
[0029] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0030] According to one aspect of the present invention, the present invention relates to a method for preparing perovskite quantum dot glass, comprising the following steps:
[0031] The mixture of the glass matrix and the microcrystalline raw material is subjected to a heat-melting treatment to obtain a molten material; the molten material is placed on a first mold, and a second mold is pressed on the molten material to perform a rapid cooling treatment to obtain a perovskite quantum dot glass;
[0032] The time of the rapid cooling treatment is 5 to 10 seconds.
[0033] The present invention adopts rapid cooling treatment, the temperature drops suddenly in a short time, the energy is quickly transferred, and the quantum dots crystallize within a few seconds; it has strong repeatability and is easy to prepare on a large scale; the prepared perovskite quantum dot glass has high quantum efficiency, good heat resistance and blue light stability, and has potential application value in the field of wide color gamut display. In one embodiment, the time of the rapid cooling treatment is 5s, 6s, 7s, 8s, 9s, 9.5s, 10s, etc.
[0034] In one embodiment, the mixture comprises the following components in parts by weight:
[0035] SiO2 25-35 parts, B2O3 28-37 parts, ZnO 8-14 parts, SrCO3 5-8 parts, NaF 5-10 parts, Cs source 5-10 parts, lead source 3-5 parts and NaBr 2-5 parts. In one embodiment, the Cs source includes at least one of cesium carbonate and cesium halide, such as cesium chloride, cesium bromide, etc. In one embodiment, the lead source includes at least one of lead halide, lead oxide and lead acetate, such as lead chloride, lead bromide, etc.
[0036] Among the raw materials of the present invention, SiO2, B2O3, ZnO, SrCO3 and NaF are borosilicate glass matrix, and Cs source, Pb source and NaBr are CsPbBr3 microcrystalline raw materials.
[0037] In one embodiment, SiO2 is 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, etc., by weight. In one embodiment, B2O3 is 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, etc., by weight. In one embodiment, ZnO is 8 parts, 9 parts, 10 parts, 10.5 parts, 11 parts, 12 parts, 13 parts, 14 parts, etc., by weight. In one embodiment, SrCO3 is 5 parts, 5.5 parts, 6 parts, 7 parts, 7.5 parts, 8 parts, etc., by weight. The addition of an appropriate amount of strontium carbonate in the present invention can enhance the fluidity of the molten glass state, make the glass network structure more fluffy, and make the quantum dots easier to crystallize. In one embodiment, NaF is 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 9 parts, 9.5 parts, 10 parts, etc., by weight. In the present invention, a suitable proportion of NaF is used to make the glass network structure more fluffy and the quantum dots easier to crystallize. The crystallization mechanism is: Cs + +Br - =CsBr;Pb 2+ +Br - =PbBr2; CsBr+PbBr2=CsPbBr3. In one embodiment, the Cs source is 5 parts, 5.5 parts, 6 parts, 7 parts, 8 parts, 8.5 parts, 9 parts, 9.6 parts, etc. by weight. In one embodiment, the Pb source is 3 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts, 4.8 parts, 5 parts, etc. by weight. NaBr is 2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts, 4.2 parts, 4.8 parts, etc.
[0038] In one embodiment, the mixture comprises the following components in parts by weight:
[0039] SiO2 26-34 parts, B2O3 29-36 parts, ZnO 7-13 parts, SrCO3 5-7 parts, NaF 6-9 parts, Cs source 6-9 parts, Pb source 3-4 parts and NaBr 2.5-4 parts.
[0040] In one embodiment, the glass matrix and the microcrystalline raw material are ground to obtain the mixture.
[0041] In one embodiment, the particle size of the mixture is 200-500 mesh, for example, 200 mesh, 300 mesh, 350 mesh, 400 mesh, 500 mesh, etc.
[0042] In one embodiment, the temperature of the hot melt treatment is 1000-1150°C, and the time of the hot melt treatment is 5-15 minutes. In one embodiment, the temperature of the hot melt treatment includes but is not limited to 1000°C, 1020°C, 1050°C, 1080°C, 1100°C, 1120°C, 1140°C or 1150°C, etc. The time of the hot melt treatment includes 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, etc. The present invention ensures the full melting of the material by specifying the temperature and time of the hot melt treatment, which is more conducive to obtaining perovskite quantum dot glass with high luminescence performance and stability.
[0043] In one embodiment, the first mold includes a copper mold and / or a graphite mold.
[0044] In one embodiment, the second molds include copper molds and / or graphite molds.
[0045] In one embodiment, the first mold and the second mold are respectively a cube and / or a cylinder.
[0046] In one embodiment, the thickness of the first mold and the second mold are 0.5 to 2 cm, respectively, and the surface areas of the first mold and the second mold for rapid cooling are 5 to 20 cm, respectively. 2 In one embodiment, the pressure applied by the second mold to the molten material is 200-500 Pa, such as 200 Pa, 250 Pa, 300 Pa, 400 Pa or 500 Pa.
[0047] In one embodiment, the surfaces of the first mold and the second mold are smooth and flat. One is used to hold the molten quantum dot glass raw material after calcination, and the other is used to quickly press the molten quantum dot glass raw material. The pressure is the gravity of the copper mold during the pressing process, and the mold is at normal room temperature.
[0048] In one embodiment, the temperature of the first mold and the second mold is 10-25°C, for example, 11°C, 12°C, 15°C, 17°C, 20°C, 22°C, 24°C, 25°C, etc.
[0049] In one embodiment, the ambient temperature of the rapid cooling treatment is 10-25° C., such as 11° C., 12° C., 15° C., 17° C., 20° C., 22° C., 24° C., 25° C., etc.
[0050] According to another aspect of the present invention, the present invention also relates to the perovskite quantum dot glass prepared by the preparation method of the perovskite quantum dot glass.
[0051] In one embodiment, the perovskite quantum dot glass prepared by the present invention has a main emission peak at 520 nm, a half-peak width of 18 nm, and a quantum efficiency (PLQY) of up to 65% under blue light excitation at a wavelength of 420 nm. It has good heat resistance and blue light stability, and has potential application value in the field of wide color gamut display.
[0052] The following is further explained in conjunction with specific embodiments and comparative examples.
[0053] Example 1
[0054] The preparation method of perovskite quantum dot glass comprises the following steps:
[0055] In an agate mortar, the glass matrix and the microcrystalline raw material are ground and mixed evenly to obtain a mixture; the mixture is placed in a corundum crucible and calcined in a box furnace at 1150°C for 10 minutes in an air atmosphere. After the calcination, the molten quantum dot glass raw material in the crucible is immediately poured onto a copper mold, and another copper mold of the same size is pressed on top for 5 seconds to fully cool it. After removing the upper copper mold, the crystallized perovskite quantum dot glass (CsPbBr3@Glass) is obtained;
[0056] The mixture includes the following components in parts by mass:
[0057] SiO2 27 parts, B2O3 35 parts, ZnO 11 parts, SrCO3 5 parts, NaF 8 parts, Cs2CO3 8 parts, PbBr2 3 parts and NaBr 3 parts;
[0058] The copper mold is a cube; the thickness is 1 cm, and the relative surface area of the two copper molds pressed together is 10 cm 2 .
[0059] Example 2
[0060] The preparation method of perovskite quantum dot glass comprises the following steps:
[0061] In an agate mortar, the glass matrix and the microcrystalline raw material are ground and mixed evenly to obtain a mixture; the mixture is placed in a corundum crucible and calcined at 1100°C in a box furnace under air atmosphere for 13 minutes. After the calcination, the molten quantum dot glass raw material in the crucible is immediately poured onto a copper mold, and another copper mold of the same size is pressed on top for 8 seconds to fully quench. After removing the upper copper mold, the crystallized perovskite quantum dot glass is obtained;
[0062] The mixture includes the following components in parts by mass:
[0063] SiO2 35 parts, B2O3 26 parts, ZnO 10 parts, SrCO3 5 parts, NaF 6 parts, Cs2CO3 8 parts, PbBr2 5 parts and NaBr 5 parts;
[0064] The copper mold is a cube; the thickness is 1 cm, and the relative surface area of the two copper molds pressed together is 10 cm 2 .
[0065] Example 3
[0066] The preparation method of perovskite quantum dot glass comprises the following steps:
[0067] In an agate mortar, the glass matrix and the microcrystalline raw material are ground and mixed evenly to obtain a mixture; the mixture is placed in a corundum crucible and calcined at 1150°C in a box furnace in an air atmosphere for 8 minutes. After the calcination, the molten quantum dot glass raw material in the crucible is immediately poured onto a copper mold, and another copper mold of the same size is pressed on top for 5 seconds to fully cool it. After removing the upper copper mold, the crystallized perovskite quantum dot glass is obtained;
[0068] The mixture includes the following components in parts by mass:
[0069] SiO2 35 parts, B2O3 30 parts, ZnO 10 parts, SrCO3 5 parts, NaF 5 parts, Cs2CO3 8 parts, PbBr2 3 parts and NaBr 4 parts;
[0070] The copper mold is a cube; the thickness is 1 cm, and the relative surface area of the two copper molds pressed together is 10 cm 2 .
[0071] Example 4
[0072] A method for preparing perovskite quantum dot glass, wherein the mixture includes the following components in parts by mass:
[0073] SiO2 32 parts, B2O3 31 parts, ZnO 10.5 parts, SrCO3 7 parts, NaF 6 parts, Cs2CO3 6 parts, PbBr2 4 parts and NaBr 2.5 parts. Other conditions are the same as in Example 1.
[0074] Example 5
[0075] A method for preparing perovskite quantum dot glass, wherein the mixture includes the following components in parts by mass:
[0076] SiO2 29 parts, B2O3 35 parts, ZnO 14 parts, SrCO3 5 parts, NaF 5 parts, Cs2CO3 6 parts, PbBr2 3 parts and NaBr 3 parts. Other conditions are the same as in Example 1.
[0077] Comparative Example 1
[0078] The preparation method of perovskite quantum dot glass comprises the following steps:
[0079] In an agate mortar, the glass matrix and the microcrystalline raw material are ground and mixed evenly to obtain a mixture; the mixture is placed in a corundum crucible, and calcined at 1150°C in a box furnace under air atmosphere for 10 minutes. After the calcination, the melted quantum dot glass raw material in the crucible is transferred to a copper mold preheated at 400°C, and after cooling, it is heat-treated in a muffle furnace at 520°C for 10 hours, and the perovskite quantum dot glass is obtained after natural cooling;
[0080] The mixture includes the following components in parts by mass:
[0081] SiO2 27 parts, B2O3 35 parts, ZnO 11 parts, SrCO3 5 parts, NaF 8 parts, Cs2CO3 8 parts, PbBr2 3 parts and NaBr 3 parts;
[0082] The copper mold is a cube; the thickness is 1 cm, and the relative surface area of the two copper molds pressed together is 10 cm 2 .
[0083] Comparative Example 2
[0084] A method for preparing perovskite quantum dot glass, wherein the mixture includes the following components in parts by mass:
[0085] SiO2 29 parts, B2O3 35 parts, ZnO 14 parts, SrCO3 5 parts, NaF 5 parts, Cs2CO3 6 parts, PbBr2 3 parts and NaBr 3 parts, other conditions are the same as Comparative Example 1.
[0086] Experimental example
[0087] like Figure 1As shown, the perovskite quantum dot glasses of Examples 1-5 and Comparative Examples 1-2 measured the characteristic emission peak of CsPbBr3 at an emission wavelength of 518nm-529nm under an excitation wavelength of 420nm. The components of Comparative Example 1 are consistent with those of Example 1, and the components of Comparative Example 2 are consistent with those of Example 5, and the calcination temperature and time are consistent. Comparative Examples 1 and 2 add annealing and heat treatment processes, but the luminescence intensity and QY decrease instead. The reason is that the quantum dots have crystallized in the glass matrix after rapid cooling, and annealing and heat treatment will cause the quantum dots to grow further in the glass matrix to irregular sizes, causing devitrification, and the wavelength is red-shifted.
[0088] like Figure 2 As shown, under the excitation of blue light with a wavelength of 420 nm, the PLQY can reach 65% with reference to the blank sample (Blank) and the perovskite quantum dot glass sample of Example 1, indicating that a relatively high PLQY can still be maintained by the rapid cooling crystallization method.
[0089] The following tests were all measured by fluorescence spectrometer, and the test sample state was quantum dot glass powder.
[0090] Table 1 Quantum dot yield
[0091] Group Quantum dot yield (%) Example 1 65 Example 2 51 Example 3 47 Example 4 36 Example 5 37 Comparative Example 1 4 Comparative Example 2 20
[0092] Table 2 Stability test results
[0093]
[0094]
[0095] It can be seen from Tables 1 and 2 that the present invention uses specific raw materials in combination with rapid cooling treatment, which causes a sudden drop in temperature in a short period of time, rapid energy transfer, and quantum dots crystallization within a few seconds. The prepared perovskite quantum dot glass has high quantum efficiency and good heat resistance and blue light stability.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing perovskite quantum dot glass, characterized in that: The following steps are involved: The mixture of the glass matrix and the microcrystalline raw material is subjected to a heat-melting treatment to obtain a molten material; the molten material is placed on a first mold, and a second mold is used to press the molten material to perform a rapid cooling treatment to obtain a perovskite quantum dot glass; The time of the rapid cooling treatment is 5 to 10 seconds; The mixture consists of the following components in parts by mass: SiO2 25~35 parts, B2O3 28~37 parts, ZnO 8~14 parts, SrCO3 5~8 parts, NaF 5~10 parts, Cs source 5~10 parts, lead source 3~5 parts and NaBr 2~5 parts.
2. The method for preparing perovskite quantum dot glass according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) The Cs source is selected from at least one of cesium carbonate and cesium halide; (2) The lead source is selected from at least one of lead halide, lead oxide and lead acetate.
3. The method for preparing perovskite quantum dot glass according to claim 2, characterized in that: The mixture consists of the following components in parts by mass: SiO2 26~34 parts, B2O3 29~36 parts, ZnO 9~13 parts, SrCO3 5~7 parts, NaF 6~9 parts, Cs source 6~9 parts, Pb source 3~4 parts and NaBr 2.5~4 parts.
4. The method for preparing perovskite quantum dot glass according to claim 1, characterized in that: The glass matrix and the microcrystalline raw material are ground to obtain the mixture.
5. The method for preparing perovskite quantum dot glass according to claim 4, characterized in that: The particle size of the mixture is 200-500 meshes.
6. The method for preparing perovskite quantum dot glass according to claim 1, characterized in that: The temperature of the hot melt treatment is 1000-1150° C., and the time of the hot melt treatment is 5-15 minutes.
7. According to the method for preparing perovskite quantum dot glass according to claim 1, the thickness of the first mold and the second mold are 0.5~2cm respectively.
8. The method for preparing perovskite quantum dot glass according to claim 1, characterized in that: The temperature of the first mold and the second mold is 10-25°C.
9. The method for preparing perovskite quantum dot glass according to claim 1, characterized in that: The ambient temperature of the rapid cooling treatment is 10-25°C.
10. The perovskite quantum dot glass prepared by the method for preparing perovskite quantum dot glass according to any one of claims 1 to 9.
Citation Information
Patent Citations
Light amplification material based on perovskite quantum dot glass as well as preparation method and application thereof
CN109809698A
Method for promoting crystallization of all-inorganic perovskite quantum dots in glass by adding fluoride
CN110194593A
Preparation method and application of efficient all-inorganic perovskite quantum dot glass
CN112047635A